A sharing economy? Unpacking demand and living conditions in the urban housing market in Kenya. (September 2018) - Gulyani, Sumila; Talukdar, Debabrata; Bassett, Ellen M.
Highlights: The majority of Kenyan urban residents are tenants and do not own any property in the country. Almost half of households share facilities, 40 percent of housing stock is designed and built for sharing. The housing quality problem? It is lack of kitchens and toilets, more than overcrowding or impermanent materials. Rents are a significant share of income, but indicate low affordability for ownership, if viewed as mortgage payments. Market valuations of unit, infrastructure and neighborhood related rent drivers vary significantly by house type and city. Abstract: With Africa's urban transition underway, housing is a formidable challenge. Housing shortfalls and continued slum growth are consistently forecast. But what kinds of housing do current residents occupy? Do owners have better quality housing than tenants? How much do tenants pay and what features do they value? This study builds a demand-side understanding of housing using survey data from over 14, 000 households in 15 Kenyan cities. Kenya's urban housing market is characterized by renting and sharing. Approximately 86 percent of residents are tenants; they outnumber owners in 14 of 15 cities. Sharing is ubiquitous—households share houses, rooms, and/or facilities such as toilets and taps. In contrast to standard notions of an "acceptable" housing unit, only 18 percent of urban Kenyans live in a self-contained unit with a toilet, kitchen, electricity, and private water connection. The market is delivering two under-studied housing categories—compounds and dormitories—explicitly designed for sharing. These house 40 percent of urban households in individual rooms, but require sharing of toilets and water connections. Rents represent a significant share of household income, but indicate low ability to achieve ownership, if viewed as monthly mortgage payments. Hedonic regression analyses reveal the relative value of house features with electricity, kitchens and number of rooms emerging as important drivers of rent. Neighborhood conditions, such as lack of flooding and perceived safety, and neighborhood level infrastructure and services, such as garbage collection and access to transport, also have positive impacts upon rents. Our analysis urges a rethinking of housing policies, including reevaluation of what type of housing is deemed acceptable and affordable for very low income urban residents. It underscores the need to develop more and better-quality rental housing and calls for a reassessment of housing and infrastructure investment programs, as well as more creative approaches for expanding home ownership.